2019
DOI: 10.1002/ajim.23016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain in migrant construction workers in Mar del Plata, Argentina

Abstract: Background We aimed to compare employment conditions, psychosocial working conditions, and prevalence of low back pain among migrant and local construction workers in Argentina. Methods In a cross‐sectional study among workers from three contracting and eight subcontracting companies as well as 26 construction sites in the region of Buenos Aires, Argentina, 134 out of 150 local (89% response) and 141 out of 150 migrant construction workers (94% response) answered a validated questionnaire. Psychosocial working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In addition to that, they clearly demonstrate the definition of migrant workers, health and risk factors and risk solutions. Limited data samples and a lack of comprehensive research validation are the limitations of current research on the health and safety of migrant workers (Machado Susseret et al, 2019;Kim et al, 2020;Mosly and Makki, 2021). The results could be beneficial to clarify the health and safety issues relevant to migrant workers in the construction industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, they clearly demonstrate the definition of migrant workers, health and risk factors and risk solutions. Limited data samples and a lack of comprehensive research validation are the limitations of current research on the health and safety of migrant workers (Machado Susseret et al, 2019;Kim et al, 2020;Mosly and Makki, 2021). The results could be beneficial to clarify the health and safety issues relevant to migrant workers in the construction industry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, due to the high mobility of migrant construction workers, it is difficult for institutions to collect statistics on all migrant construction workers (Dong and Platner, 2004). In addition to that, some construction companies may hide incidents or refuse to participate in research and some migrant workers may deliberately conceal true information to keep their jobs (Machado Susseret et al, 2019). In order to promote the health and safety of migrant workers in the construction sector, factors that contribute to the increased safety risks need to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…The job demand increases due to over-commitment at work and moderated by rewards. Both later variables are also known as part of the effort-reward imbalance (ERI) components which, if not adjusted properly, may lead to low back pain (N Machado Susseret et al, 2019). Other health conditions are also affected by job demand as it is demonstrated that job demand is positively associated with diastolic blood pressure, work absence, and experience of pain or discomfort (Bodner et al, 2014).…”
Section: Job Demandsmentioning
confidence: 99%
“…Again, ERI factors may be involved in this job dissatisfaction, because when skilled workers are involved, they often do not practice their specialty and, thus, their supervisor does not appreciate their work and skill (Jebens et al, 2014). Workers who do not have a working contract and working more than 44 hours per week also have a high ERI score (N Machado Susseret et al, 2019).…”
Section: Job Dissatisfactionmentioning
confidence: 99%
“…This is due to the effort-reward imbalance, 82% for migrants and only 19% for locals. In [6] the working conditions of 349 people who attended the trauma area in Valencia, Spain, was analyzed. The main result was a positive correlation between the manual lifting of loads and the days of disability, without counting the age and gender of the participants.…”
Section: Introductionmentioning
confidence: 99%